2020
DOI: 10.1021/acsanm.0c01819
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanorod-Based Bio-Barcode Sensor Array for Enzymatic Detection in Biomedical Applications

Abstract: Early diagnosis of disease onset requires sensor systems that detect multiple disease-related processes within the body. However, major obstacles must be surmounted for in vivo sensor use, including size, biocompatibility, sensitivity, and selectivity. As an initial study, here we fabricated a multidimensional gold nanorod (GNR)-based bio-barcode sensing array for sensitive and selective detection of biological events. The sensor comprises an array of gold nanocavities and GNRs that are bound to the array as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…These molecular logic gates are superior to their semiconductor comparable as they can provide different information available to molecular logic as opposed to voltage information only [ 14 ]. The input can be physical (temperature [ 15 ], pressure [ 16 ], pH [ 17 ], light [ 18 ]), biochemical (enzymes [ 19 , 20 ] nucleotides [ 21 ]), and chemical (atomic [ 12 ], molecular [ 22 ]). For molecular computing, it is essential to design the logic gates using nano regime electronic circuits.…”
Section: Introductionmentioning
confidence: 99%
“…These molecular logic gates are superior to their semiconductor comparable as they can provide different information available to molecular logic as opposed to voltage information only [ 14 ]. The input can be physical (temperature [ 15 ], pressure [ 16 ], pH [ 17 ], light [ 18 ]), biochemical (enzymes [ 19 , 20 ] nucleotides [ 21 ]), and chemical (atomic [ 12 ], molecular [ 22 ]). For molecular computing, it is essential to design the logic gates using nano regime electronic circuits.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of a target analyte to a plasmonic nanocavity array is sensed by spectral variation in the plasmonic resonance observed at either transmission maxima or transmission minima . In particular, gold plasmonic nanocavity arrays of various types have distinct surface plasmon resonance (SPR) and are used for nanoplasmonic biosensing due to their biocompatibility and absorption spectrum in a visible range. , …”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of plasmonic nanocavity arrays over conventional SPR schemes, such as portability and multiplexing capabilities, they generally have a lower bulk sensitivity . The biosensing capabilities of such nanocavity arrays can be improved by enhancing the spectral variations in response to a target molecule binding. , To this end, efforts have focused on varying the thickness as well as the cavity size, structure, and periodicity of the nanocavity array, which affect their transmission spectrum and generate different plasmonic modes. Another attractive approach for enhancing the spectral variation of nanocavity arrays is by incorporating gold nanorods (GNRs), which have unique optical properties that enhance spectroscopic processes. ,,, We previously demonstrated that GNRs conjugated to a gold nanocavity array enable biomarker detection for biosensing applications …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations